2013
DOI: 10.1084/jem.20121416
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 promotes immune exhaustion by inducing antiviral T cell motility paralysis

Abstract: PD-L1 decreases anti-viral CD8+ T cell motility and PD-1 blockade restores motility in the presence of high viral loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
192
4
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(220 citation statements)
references
References 73 publications
12
192
4
5
Order By: Relevance
“…In contrast, Ruocco and colleagues (16) concluded that a-CTLA-4 antibodies fail to generate protective tumor immunity and must be combined with radiation because anti-CTLA-4 treatment increases T-cell motility. Unlike these earlier reports, our findings are more consistent with the conclusion that the antibodies mediate their positive effects on tumor immunity by blocking CTLA-4-mediated inhibition and enhancing T-cell motility in tumors, similar to the reversal of the exhausted T-cell motility paralysis during chronic viral infections (18).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In contrast, Ruocco and colleagues (16) concluded that a-CTLA-4 antibodies fail to generate protective tumor immunity and must be combined with radiation because anti-CTLA-4 treatment increases T-cell motility. Unlike these earlier reports, our findings are more consistent with the conclusion that the antibodies mediate their positive effects on tumor immunity by blocking CTLA-4-mediated inhibition and enhancing T-cell motility in tumors, similar to the reversal of the exhausted T-cell motility paralysis during chronic viral infections (18).…”
Section: Discussionsupporting
confidence: 90%
“…This conclusion is in direct opposition to the current model of CTLA-4-mediated inhibition via the reversal of the TCR-induced stop signal (17). Instead, our observations resemble the recently described reversal of the antiviral T-cell motility paralysis by PD-1-specific antibodies during T-cell exhaustion in persistent viral infections (18).…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations